Comportamento de propriedades físicas e químicas de dois latossolos roxos sob diferentes sistemas de rotação de culturas em plantio direto - Santos, Júlio Cézar Franchini (1993)
The purpose of this study was to evaluate, after 7.5 years (1985-1992), the effects of some crop rotations in no-tillage systems, in relation to soybean-wheat (Glycine max-Triticum aestivum) in conventional tillage (disc plough) (CT), on the physical proprieties and fertility leveis of an eutrophic "Latosol Roxo" (Oxisol) in Londrina, PR, and an alic "Latosol Roxo" in Campo Mourão, PR, Brazil, as well as the effects on wheat yield. The following crop rotation treatments in no-tillage systems were evaluated: SW, soybean-wheat; OAT, oat (Avena strigosa)- soybean-wheat; LMOSW, lupin (Lupinus angustifolius)-maize (Zea mays)-oat-soybean-wheat; LMSW, lupin-maize-soybean-wheat. In both places the results were compared with soil under natural vegetation. There was an increase in bulk density (BD) under OAT, in the 0-5 cm depth, which caused an increase in MIP (microporosity) and reduced TP (total porosity) , MAP (macroporosity) and Ks (saturated hydraulic conduetivity); changes in these parameters could be possibly related with the use of roller knife in the oat crop. Although the same practice has been also used in the lupin crop, soil compactive effect was reduced by the root system of this legume. The geometric mean diameter (GMD) of the soil aggregates was increased by the use of green manure winter crop, specially by the lupin in the LMSW crop rotation, resulting in increases, in relation to the CT system, of 25.9% in Campo Mourão and of 64.8% in Londrina, where the stability of the soil aggregates was more affected by the continuous soil cultivation. The stability of the soil aggregates was positively correlated with organic C and total N in soil and in greater than 4.0 mm aggregates in Londrina, but only with total N in soil and in greater than 4.0 mm aggregates in Campo Mourão, where the decrease in pH and the increase in Al and H+Al contents were better and positively correlated with the stability of the soil aggregates. No-tillage systems allowed increases, in relation to the conventional tillage, in pH, organic C, and total N in the surface soil (0-4 cm depth) . These effects were less intense with the use of green manure winter crops, what was partially associated with absence of inorganic fertilization. The contribution of organic C to CEC at pH 7.0 was higher in Campo Mourão (4.60 meq/g) than in Londrina (3.68 meq/g). When lupin was present in the LMSW system there was an increase in wheat yield of 8% (275 kg/ha) in Londrina and of 44% (475 kg/ha, statistically significant) in Campo Mourão in relation to SW. Yield was positively correlated with the increase in total N content (0-40 cm depth), and with the increase in GMD (0-10 cm depth), and both parameters were higher in LMSW rotation. In the soil and plant management carried out in this experiment the soil structure was better related with wheat yield than the soil fertility parameters measured. The results obtained in this work suggest that crop diversity in rotation systems, with differences in root systems and plant residues can promote the recovery of soil physical proprieties and fertility levels, allowing a favorable environment to the development of crops.